21st century business : - Cortada, James W. (Financial Times/​Prentice Hall, 2001)
As Oracle Corporation reminds us in their slogan: "the Internet Changes Everything". Or as Buick said in its advertising a couple of years ago: "This isn't your father's Buick". The world of work and managing has changed dramatically over the past decade, requiring a new kind of manager, a new kind of worker and a new understanding of the way of work in this so-called post-industrial world. Cortada lays out the issues that come to play in this new world, and some guidelines and precepts for navigating the new world's seas.